A survey of the economic role of software platforms in computer-based industries - David S. Evans; Andrei Hagiu; Richard Schmalensee (Center for Economic Studies and ifo Institute (CESifo), 2004)
Software platforms are a critical component of the computer systems underpinning leading? edge products ranging from third? generation mobile phones to video games. After describing some key economic features of computer systems and software platforms, the paper presents case studies of personal computers, video games, personal digital assistants, smart mobile phones, and digital content devices. It then compares several economic aspects of these businesses including their industry evolution, pricing structures, and degrees of integration.
Keywords: L15; L11; L86; 330; software platforms; hardware platforms; network effects; bundling; multi-sided markets; IT-Industrie; Mobilkommunikation; Unterhaltungselektronik; Software; Price bundling; Japan